2011
DOI: 10.3171/2011.3.spine10911
|View full text |Cite
|
Sign up to set email alerts
|

Functional restoration of the paralyzed diaphragm in high cervical quadriplegia via phrenic nerve neurotization utilizing the functional spinal accessory nerve

Abstract: The authors report a case of functional improvement of the paralyzed diaphragm in high cervical quadriplegia via phrenic nerve neurotization using a functional spinal accessory nerve. Complete spinal cord injury at the C-2 level was diagnosed in a 44-year-old man. Left diaphragm activity was decreased, and the right diaphragm was completely paralyzed. When the level of metabolism or activity (for example, fever, sitting, or speech) slightly increased, dyspnea occurred. The patient underwent neurotizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Application of peripheral nerve transfers for SCI is not new. 3 4 11 26 27 28 29 30 31 32 33 34 Most clinical applications have utilized intercostal nerve roots proximal to the SCI to reinnervate lumbar plexus nerve. The nerve transfer strategies for the treatment of cervical SCI are relatively sparse, especially for restoration of hand function.…”
Section: Discussionmentioning
confidence: 99%
“…Application of peripheral nerve transfers for SCI is not new. 3 4 11 26 27 28 29 30 31 32 33 34 Most clinical applications have utilized intercostal nerve roots proximal to the SCI to reinnervate lumbar plexus nerve. The nerve transfer strategies for the treatment of cervical SCI are relatively sparse, especially for restoration of hand function.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up of patients on which this type of procedure has been carried out have demonstrated optimal results . To the best of our knowledge, there have been no reports in the literature which have focused on the technique we performed here, even though some teams have proposed other approaches such as neurotization of the phrenic nerve with the trapezius branch of the ipsilateral spinal accessory nerve, or reconstruction of the phrenic nerve employing fibers of sural nerve . In the light of chemotherapeutic failure in this patient, a surgical option was derived from a MDT decision, and this approach enabled removal of the tumor which offered a better life expectancy, as well as achieving spontaneous breathing effort.…”
Section: Discussionmentioning
confidence: 98%
“…The spinal accessory nerve (SAN) has been shown to be a possible donor nerve for anastomosis with the PN to restore physiological respiration. 9,28,29,31 However, the SAN does not have spontaneous discharge, and an external electronic pacing has to be provided. Spontaneous discharge from a donor nerve is important for restoration of spontaneous respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal accessory nerve (SAN) and PN anastomosis has been shown to be a possible way to restore the respiratory movement of the diaphragm. 9,28,29,31 Our previous study showed that vagus nerve (VN) to PN anastomosis could partially improve respiratory function in rabbits that had been subjected to unilateral PN transection. 30 Nevertheless, there are drawbacks to using the VN for anastomosis to the PN, even though the VN contains some fibers that produce efferent discharges synchronous with the PN.…”
mentioning
confidence: 99%